Pemanfaatan Jurnal Elektronik (E-Journal) di Perpustakaan Universitas Negeri Padang - Angelina, Aliffia; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThe study of this research in about Utilization of Electronic Journal by Librarian in Library of State University of Padang. To describe the efforts of librarians in improving the utilization of Electronic Journals in the Library of State University of Padang. Data collected through interviews with librarian. Analyzing data is done by distributing questionnaires. The first use of Electronic Journals in the Library of State University of Padang. The second problems of users in utilization Electronic Journals in the Library of State University of Padang. The third effort of librarians in improving Electronic Journals in the Library of State University of Padang.Keywords : electronic journals, user of library, librarians.